Regulation of Phosphatidylcholine Biosynthesis in Saccharomyces cerevisiae - Waechter, Charles J. (1971)
Evidence is presented which indicates that the biosynthesis of phosphatidylcholine by the methylation pathway in growing cultures of Saccharomyces cerevisiae is repressed by the presence of choline in the growth medium. This result, obtained previously for glucose-grown cells, was also observed for lactate-grown cells, of which half of the phosphatidylcholine is mitochondrial. A respiration-deficient mutant of the parent wild-type strain has been studied, and its inability to form functional mitochondria cannot be due to an impaired methylation pathway, as it has been shown to incorporate (14)C-CH(3)-methionine into all of the methylated glycerophosphatides. The incorporation rate is depressed by the inclusion of 1 mm choline in the growth medium, suggesting a regulatory effect similar to that demonstrated for the wild-type strain. The effects of choline on the glycerophospholipid composition of lactate and glucose-grown cells is presented. The repressive effects of the two related bases, mono- and dimethylethanolamine, were examined, and reduced levels of (14)C-CH(3)-methionine incorporation were found for cells grown in the presence of these bases. The effect of choline on the methylation rates is reversible and glucosegrown cells regain the nonrepressed level of methylation activity in 60 to 80 min after removal of choline from the growth medium.